2021
DOI: 10.3390/molecules26020285
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Volatile Compound Profiles in Cold-Pressed Oils Obtained from Various Seeds during Accelerated Storage

Abstract: Cold-pressed oils are highly valuable sources of unsaturated fatty acids which are prone to oxidation processes, resulting in the formation of lipid oxidation products, which may deteriorate the sensory quality of the produced oil. The aim of the study was to determine the main volatile compounds which differentiate examined oils and could be used as the markers of lipid oxidation in various oils. In the experiment, cold-pressed oils—brown flaxseed, golden flaxseed, hempseed, milk thistle, black cumin, pumpkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…From the study design perspective, a very important question was that the fatty acid profile of the milk thistle seeds and milk thistle seed oil was similar. The main PUFA of the seeds and oil was linoleic acid (53.0% and 55.1%, respectively), and these results were generally in agreement with the literature 13 , 32 . Moreover, the seeds and oil were a relatively poor source of α -linolenic acid (0.12% and 0.13%, respectively) and similar proportions of this fatty acid were determined by Zarrouk et al 32 and Rokosik et al 30 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…From the study design perspective, a very important question was that the fatty acid profile of the milk thistle seeds and milk thistle seed oil was similar. The main PUFA of the seeds and oil was linoleic acid (53.0% and 55.1%, respectively), and these results were generally in agreement with the literature 13 , 32 . Moreover, the seeds and oil were a relatively poor source of α -linolenic acid (0.12% and 0.13%, respectively) and similar proportions of this fatty acid were determined by Zarrouk et al 32 and Rokosik et al 30 .…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, Zhang et al 31 also reported that the milk thistle seed oil can be a good source of MUFAs, which can comprise over 30% of total fatty acids, and this proportion was higher than that of the present study both for the seeds and oil (24.7% and 23.7%, respectively). According to the literature, the main MUFA in the milk thistle seed oil is oleic acid 13 , which equaled 24.1% of total fatty acids, and comparable proportions of this acid was also determined in this study (23–24%).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Oil deterioration is mainly associated with volatile compounds such as aldehydes, ketones, esters, and furan derivatives, which are formed as a result of lipid oxidation processes [47,48], especially the auto-oxidation of unsaturated fatty acids. Several compounds, including hexanal or nonanal, are used as markers to detect the oxidation of lipids [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported for sunflower seeds [34] with 5.00-6.10% of palmitic, 2.53-3.24% of stearic, 54.1-54.1% of oleic, and 32.3-41.0% of linoleic fatty acids. Additionally, other seeds such as hemp, pumpkin, brown flaxseed, golden flaxseed, blue poppy seed, and white poppy seed oils have shown similar fatty acid composition [35][36][37]. Regarding fried samples, linoleic acid (77.40 ± 0.02%) was the highest fatty acid at the beginning of the storage period followed by oleic (14.31 ± 0.02%), palmitic (4.56 ± 0.19%), and, finally, stearic (3.73 ± 0.15%) acids.…”
Section: Quantitative Analysis Of Famesmentioning
confidence: 99%